Regulation of Pyrimidine and Arginine Biosynthesis Investigated by the Use of Phaseolotoxin and 5-Fluorouracil - Jacques, Steve (1981)
Purified phaseolotoxin inhibits the growth of carrot cells. Such inhibitions can be reversed completely by citrulline but not by arginine. This toxin inhibits ornithine transcarbamylase activity in vitro, which leads to an accumulation of ornithine and a decrease in arginine levels intracellularly. In carrot cells, 5-fluorouracil (5-FU) toxicity can be reduced by the addition of purified toxin and citrulline, or ornithine. The toxin also decreases the incorporation of [(14)C]uracil and [(14)C]5-FU into trichloroacetic acid precipitable material by 50%. Finally, a 5-FU-resistant line, F5 (Sung ZR, Jacques S 1980 Planta 148: 389-396), was found to be more sensitive to the toxin than were 5-FU-sensitive cells. One millimolar 5-FU roughly doubled the ability of F5 to tolerate phaseolotoxin. These results demonstrate a close regulation between the pyrimidine and arginine path-ways in carrots.